Population Survey And Potential Utilization Of Opuntia ficus-indica (Prickly Pear Cactus) in Drylands of Kupang Regency, East Nusa Tenggara - Pither Yesend Boimau; Daniel H Wadu; Jidon AY Nubatonis (IRDH International Journal of Technology, Agriculture and Natural Sciences, 2026)
The aim of this study is to analyze the spatial distribution of the population and examine the level and forms of utilization of prickly pear cactus (Opuntia ficus-indica) by the community in Kupang Regency, NTT. This plant has been proven to grow well in marginal drylands, making it an important biomass resource. The method used was a field survey employing quadrats for population density estimation and structured ethnobotanical interviews across three ecological zones (Coastal, Medium Hills, and Dry Uplands). Spatial analysis was conducted using Geographic Information Systems (GIS) to map distribution. The main result shows that Opuntia ficus-indica has a high population density (highest in the Hills Zone: (190 ±  25 Ind/Ha). However, the level of utilization for economic and nutritional value is very low: 91% of respondents only use it as a living fence, 0% use it as livestock feed, and only 2% make use of it as a medicinal plant. The data also indicate an information gap, where 10% of respondents explicitly stated that they did not know any other benefits of this plant besides its physical function. The conclusion emphasizes a significant contradiction between the plant's abundant ecological potential and the minimal adoption of its use. Immediate interventions are needed in the form of introducing thornless varieties and enhancing education to optimize the utilization of Opuntia ficus-indica in Kupang Regency.